1985
DOI: 10.1007/bf02552653
|View full text |Cite
|
Sign up to set email alerts
|

Are postoperative fever and/or septic complications prognostic factors in colorectal cancer resected for cure?

Abstract: The authors have examined the survival rate of 111 patients with colorectal cancer (Dukes' A, B, and C stages) treated by potentially curative surgery. In particular, the survival has been evaluated with regard to the appearance of postoperative fever and/or septic complications. The preliminary results demonstrate that these factors do not significantly influence the long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
2
11
0
1
Order By: Relevance
“…Fucini et al (1985), Sauven et al (1989) and Kressner et al (2002) reported increased local recurrence in colorectal cancers after perineal wound infection similar to the report of Varty et al (1994). They found no difference in overall survival and concluded that there was no overall survival difference for patients with or without postoperative sepsis following excision of colorectal cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Fucini et al (1985), Sauven et al (1989) and Kressner et al (2002) reported increased local recurrence in colorectal cancers after perineal wound infection similar to the report of Varty et al (1994). They found no difference in overall survival and concluded that there was no overall survival difference for patients with or without postoperative sepsis following excision of colorectal cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Increasing evidence has shown that postoperative complications due to infection, especially those caused by anastomotic leakage after colorectal surgery, were significantly associated with a negative long-term outcome (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Two reports on the impact of postoperative fever on survival in patients with colorectal cancer yielded contradictory results. 6,7 In one retrospective study of 227 patients who underwent curative surgery, Nowacki and Szymendera 6 found that postoperative fever, was the most unfavorable prognostic factor, followed by disease stage. However, the results of that study could not be replicated in a later study of 111 colorectal cancer patients, 7 and the question remained unanswered for the following two decades.…”
mentioning
confidence: 99%